Teaching and Learning with Technology: The Effectiveness of ICT Integration in Schools (Journal of Pharmaceutical Negative Results, 2022)
The integration of information, communication and technology (ICTs) will help teachers meet the global need to replace traditional teaching methods with technology-based learning tools and mediums. In Uzbekistan, ICT is seen as one of the main elements of the country's transformation towards future development. The Ministry of Higher and Special Education is aware of the importance of technology-based teaching and learning in the national curriculum of schools. The aim of this study is to analyse teachers' perceptions of the effectiveness of ICT integration to support teaching and learning in the classroom.